If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 * 3 + -3y = -7 Multiply -2 * 3 -6 + -3y = -7 Solving -6 + -3y = -7 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -3y = -7 + 6 Combine like terms: -6 + 6 = 0 0 + -3y = -7 + 6 -3y = -7 + 6 Combine like terms: -7 + 6 = -1 -3y = -1 Divide each side by '-3'. y = 0.3333333333 Simplifying y = 0.3333333333
| 4w-22=8w-70 | | 4x+8x^2=9 | | -17g-4=14-8g | | log(45/x)=0.34 | | -96=-6g+2g | | -2*4-3y=-7 | | 2x-24x=-72 | | -8h+10=-9h+18 | | p^2-2p=-1 | | -9f-6f=24 | | -2*2-3y=-7 | | X^5=65 | | 6=v+5v | | 48=5y-12 | | -3-4z=-15 | | 9x-6=12x-3x | | 3(-2x-1)=2x+5 | | 4(1+5g)= | | 4x+12+2x= | | 4(1+5g)=Submit | | (5x-2)+(2x+8)+90=180 | | 11j-6j+4j=18 | | 7(4p+1)= | | 2x^5=130 | | 2(1+3n)= | | 5(2+5h)= | | 4x-5=-x-5 | | 135x=4 | | 8m-29=59 | | 4x+12+3x= | | X=y-35 | | 3q+5q=48 |